1995
DOI: 10.1111/j.1365-2672.1995.tb02841.x
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of plasmids between strains of Escherichia coli under rumen conditions

Abstract: Strains of Escherichia coli originally isolated from the rumen of sheep were shown to be capable of exchanging a 60kb plasmid, conferring resistance to tetracycline and ampicillin, at low frequencies (below 10(-6) per recipient) under anaerobic conditions in the presence of (a) autoclaved and clarified rumen fluid, (b) raw clarified rumen fluid, or (c) whole rumen fluid. Under anaerobic conditions the two rumen strains showed no inhibition of growth rate when 50 mmol l-1 volatile fatty acids were added to LB m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 18 publications
0
31
0
Order By: Relevance
“…Relatively early in the understanding of rumen microbiology, Wolin (1969) reported that VFA were more inhibitory to the growth of E. coli than of other rumen bacteria. Since then, the occurrence of relatively low numbers of E. coli in the ruminant gut has been ascribed to the inhibitory effects of VFA, and more recent work has supported this view (Rasmussen et al 1993;Scott and Flint 1995). It is often difficult to unravel some of the reported effects of the diet and animal husbandry practice from effects of VFA.…”
Section: Effects Of Weak Acidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Relatively early in the understanding of rumen microbiology, Wolin (1969) reported that VFA were more inhibitory to the growth of E. coli than of other rumen bacteria. Since then, the occurrence of relatively low numbers of E. coli in the ruminant gut has been ascribed to the inhibitory effects of VFA, and more recent work has supported this view (Rasmussen et al 1993;Scott and Flint 1995). It is often difficult to unravel some of the reported effects of the diet and animal husbandry practice from effects of VFA.…”
Section: Effects Of Weak Acidsmentioning
confidence: 99%
“…However, E. coli K-12 is not representative of either commensal or E. coli0157 strains, as strains of E. coli K-12 lack some of the long-chain lipopolysaccharides (LPS) which confer protection on strains of E. coli, including 0157. For example, Scott and Flint (1995) found that some ovine rumen commensal strains of E. coli were able to grow at normal rates in anaerobic media at pH 7 in the presence of 50 mmol 1-1 VFA, whereas growth of a laboratory K-12 strain was completely inhibited under these conditions. A VFA concentration of 100mmol 1-1 was inhibitory to growth of the rumen strains, particularly at pH 6, and tolerance of VFA was greatest under aerobic growth conditions.…”
Section: Effects Of Weak Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless Scott and Flint [70] demonstrated conjugative transfer of an antibiotic resistance plasmid between two strains of E. coli under anaerobic conditions in the presence of whole rumen contents. Transfer occurred at substantially lower rates compared with clue to the tetW origin may lie in its higher DNA % G +C content compared with other ribosome protection genes, but it is currently unclear whether tetW is a recent acquisition from soil microorganisms, or a long standing resident within the gut microbial community.…”
Section: Conjugal Transfermentioning
confidence: 99%
“…fibrisolvens [25] and Selenomonas ruminantium [26] have plasmids been found that are large enough to carry significant amounts of information beyond the genes necessary for their own replication and maintenance. Plasmid transfer in the presence of a complete rumen flora has been demonstrated only for rumen E. coli [27]. Recent work has demonstrated natural, high frequency transfer of a tetracycline resistance determinant between strains of Bu.…”
mentioning
confidence: 99%